Enhancing Road-Based Supply Chain Efficiency in the US: Integrating AI/ML-Based C3I Systems with IoT-Enabled Trucks - Singh, Sukhdeep (International Journal of Supply Chain Management, 2024)
This paper explores the integration of AI/ML- based C3I systems with IoT-enabled trucks to enhance the efficiency of road-based supply chains in the US. By examining the components and benefits of these technologies, as well as their implementation strategies and real-world applications, this paper provides a comprehensive overview of how these advancements can transform supply chain logistics. The author has been at the forefront of crafting an IoT sensor-based Fleet and Transportation Management System for one of the top 10 telematics companies. It utilizes AI and ML to provide strategic and operational insights within a logistics environment for the complete paradigm ranging from SMB to enterprise level companies. The discussion covers operational benefits such as reduced downtime and optimized routing, and strategic advantages including improved decision-making and increased resilience against disruptions. Ultimately, the goal is to highlight how these innovations can drive significant improvements in the performance and reliability of road-based supply chains, leading to lower costs and better profits.